2011
DOI: 10.1021/op100270u
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Robust Process for a CRF1 Receptor Antagonist

Abstract: A scalable and robust process was developed for the preparation of pexacerfont (2), a pyrazolotriazine corticotropin-releasing factor receptor 1 antagonist (CRF1). The formation of the core hydroxypyrazolotriazine moiety was achieved through two consecutive cyclizations of a semicarbazide, employing reaction conditions that are significantly milder than those reported in the literature. Further conversion to the key chloropyrazolotriazine intermediate was accomplished through a novel catalytic process using ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The major impurity was identified as the condensate 27 (up to 10%, Scheme 5). Addition of catalytic DABCO 22 significantly increased the rate of conversion while suppressing the formation of 27, resulting in an improved yield of chloride 24 (90% in-process yield). Mechanistic studies indicated that multiple phosphoryl intermediates rapidly formed in the first stage of the reaction.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…The major impurity was identified as the condensate 27 (up to 10%, Scheme 5). Addition of catalytic DABCO 22 significantly increased the rate of conversion while suppressing the formation of 27, resulting in an improved yield of chloride 24 (90% in-process yield). Mechanistic studies indicated that multiple phosphoryl intermediates rapidly formed in the first stage of the reaction.…”
Section: T H Imentioning
confidence: 99%
“…It is recommended that this compound be handled at lower than 50 °C.) This process was successfully implemented at our contract manufacturing site (five batches, 75 kg input of benzyl carbazate), providing 563 kg of the product with >99% HPLC purity: Diethyl 1-(Benzyloxycarbonylamino)-1H-pyrrole-2,3dicarboxylate (22). To a slurry of sodium diethyl oxalacetate (516 g, 2.33 mol) in toluene (8.0 L) was added glacial acetic acid (7.4 mL, 0.13 mol) at 20 °C.…”
Section: ■ Conclusionmentioning
confidence: 99%
“… This reaction condition was simple, but the low solubility of monochloride as the intermediate was taken into consideration to establish the addition method of the reagents; thereby, each quarter of 11 was added to the reaction mixture at regular intervals. Unfortunately, i -Pr 2 NEt as an additive to the reaction mixture accelerated the dimerization of 12 (up to 20% relative HPLC area %) . Dichloride 12 was crystallized from the resulting mixture after quenching the remaining POCl 3 by pouring it to another reactor containing water (584 kJ/mol per 11 ) with control of the pH of the resulting suspension (pH 4–5)…”
Section: Resultsmentioning
confidence: 99%
“…The compound 1 is an intermediate in the synthesis of 8‐(6‐methoxy‐2‐methylpyridin‐3‐yl)‐2,7‐dimethylpyrazolo[1,5‐ a ][1,3,5]triazin‐4‐ol ( 5 ) as shown in Scheme . While monitoring the conversion of 1 to 5 (Scheme ), approximately 10% of an unknown species is observed within 1–2 h; however, it disappears over time (>3 h).…”
Section: Resultsmentioning
confidence: 99%